The Relationship between Grades Four to Six Students’ Perceptions towards Montessori Teaching Method and Their Achievement at Mahachai Christian Wittaya School, Thailand - Basumatary, David; Ye, Yan (Scholar: Human Sciences, 2016)
The primary purpose of this research study was to investigate students’ perceptions towards Montessori teaching method and whether there is any relationship between students’ perceptions towards Montessori teaching method and their academic achievement. The study was conducted upon grade 4, 5 and 6 students at Mahachai Christian Wittaya School, Mahachai, Thailand in a Montessori setting. A questionnaire was used for data collection and 97 students completed the surveys that measured their perceptions towards Montessori teaching method. The data analysis showed that the students’ perceptions were positive. A one-way ANOVA indicated that statistically no significant difference in the perceptions towards Montessori teaching method existed between the three groups. It was found that the students were most positive towards the construct of challenge and were not sure of their positions towards control and captivate, which had the lowest mean scores. Students’ GPAs were found to be very good. A Pearson Correlation conducted to investigate the relationship between students’ perceptions and their achievement found the existence of a strong positive relationship between students’ perceptions and their achievement levels and supports previous research. It is recommended that Mahachai Christian Wittaya School could use current data to plan future changes and improvements and consider students’ perceptions in future strategies. Future research should investigate the constructs of control and captivate to find out the effects of these variables upon student performance.